Two New Armtype Polyoxometalates Grafted on Titanium Dioxide Films: Towards Enhanced Photoelectrochemical Performance. Issue 10 (21st April 2016) - Sun, Hang; Guo, Li‐Ying; Li, Jian‐Sheng; Bai, Jian‐Ping; Su, Fang; Zhang, Lan‐Cui; Sang, Xiao‐Jing; You, Wan‐Sheng; Zhu, Zai‐Ming
Abstract: Two new carboxyethyltin‐functionalized polyoxometalates (POMs) were successfully obtained and confirmed with physicochemical and spectroscopic methods including X‐ray crystallography. The lowest unoccupied molecular orbitals of both compounds are higher in energy than that of TiO2, and the optical band gaps of these compounds are smaller than that of TiO2 . Grafting them onto a TiO2 film created two kinds of novel photoanode materials that showed significantly enhanced photovoltaic and photocurrent responses, as well as improved photoelectrooxidation activities for methanol relative to that shown by a single TiO2 film. Further, P2 W15 ‐Co‐SnR produced the largest photocurrent by exploring the photoelectric activities of a series of carboxyethyltin POM derivatives. This work provides new insight into the photoelectrochemical functionalization of POM‐based organic–inorganic hybrids. Abstract : Get grafting : Two new carboxyethyltin‐functionalized armtype polyoxometalates (POMs) are designed to be grafted on TiO2 film; this has resulted in two novel kinds of photoanote materials with enhanced photocurrent and photoelectrocatalytic activity for methanol.